Qualidade de Vida, Saúde Geral e Ansiedade em pacientes com diferentes tipos e graus de severidade de disfunção temporomandibular - Coelho, Lidiane Thomaz (2009)
Some studies reported in the literature that emotional factors and quality of life may be involved both in aetiology, as in the progression of Temporomandibular disorders (TMD). Proposition: The purpose of this study is to observe a possible association between different forms of anxiety, quality of life and general health of patients diagnosed as carriers of various types and levels of Temporomandibular Dysfunction. Methodology: The sample consisted of 60 patients diagnosed as carriers of TMJD origin of muscle, joint, or both, with different levels of severity (mild TMD, moderate and severe). The patients were diagnosed with TMD-RDC (Research Diagnostic Criteria) to assess the type of dysfunction (muscle or joint) and by the Protocol of Fonseca to verify the degree of dysfunction (mild, moderate or severe). To evaluate the psychosocial aspects were used three self-applied, with the purpose of obtaining information about the general health (General Health Questionnaire - GHQ), the type of anxiety (Trait Anxiety Inventory-State - STAI) and quality of life (World Health Organization Quality Of Life Short WHOQOL-brief). Results: There was a correlation between all indicators studied in several forms of TMD with varying degrees of commitment. Quality of life appeared linked to the type and the level of TMD: Muscular and Articular TMD (p = 0,037), Disk Displacement With Reduction (p = 0.01) and Mild TMD (p = 0.042). The General Health showed association with the level of TMD, with the exception of the stress factor (p = 0.78). For the analysis of the types and levels to Severe Muscular TMD had a statistically significant indicator of the quality of life (p = 0049). The anxiety only showed association with the level of TMD (p = 0,047 for anxiety-trait). Conclusion: Besides the limitations of the study, it was concluded that anxiety, quality of life and general health are important psychosocial indicators, which are linked to several forms of TMD in different levels of severity